Efek Latihan Fisik Jangka Pendek yang Teratur dan Terukur terhadap Kadar High Sensitivity C-Reactive Protein pada Pasien Infark Miokard Akut - Kurniawan Iskandarsyah (Jurnal Kardiologi Indonesia, 2007)
Background. Inflammation process plays an important role in the mechanism of acute coronary syndrome (ACS).  High-sensitive C-reactive protein (hs-CRP) is an inflammatory marker and a strong predictor for cardiovascular events in patients with ACS. Previous studies have shown that half of the patients with ACS has high levels of hsCRP. This study aim to prove that the short-term, low-intensity exercise training will reduce the plasma levels of hs-CRP in patients with acute myocardial infarction.Methods and results.Thirty two male patients with acute myocardial infarction were randomized into 2 groups. The first group acquired programmed exercise training with low intensity for 5 days, while the control group did not get exercise training. Before and after this exercise training, all patients in both group did treadmill test with modified Bruce protocol. Plasma hs-CRP was examined before and after the treatment. The baseline characteristics of patients in both groups did not differ significantly. There was no significant different in the baseline levels of hs-CRP between treatment and control groups. Treadmill test significantly decreased the hs-CRP levels in both groups. Although exercise training also reduced hs-CRP levels, the reduction of hs-CRP were not different between treatment group and controls.Conclusions. This study showed that short-term, low-intensity exercise training has no effect on the levels of hs-CRP in patients with acute myocardial infarction.